Quick-charging type composite coated graphite negative electrode material and preparation method thereof

By adopting composite coating technology on the surface of graphite negative electrode material, combining soft and hard carbon and carbon nanotubes/graphene, the existing graphite negative electrode materials have been solved inadequate performance in fast charging and low temperature environments, achieving high energy density and stability, and are suitable for the production of high-performance battery negative electrode materials.

CN119833593APending Publication Date: 2025-04-15CHENGDU EMINENT NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411870683.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing graphite anode materials have insufficient performance in fast charging and low temperature environments, and the materials coated with single soft carbon or hard carbon have problems with low efficiency, cycle stability and capacity for the first time.

Method used

Composite coating technology is used to coat soft and hard carbon composite materials on the surface of graphite single particles, and carbon nanotubes and/or graphene are added to improve the fast charging performance of the material by optimizing particle size and controlling graphitization and carbonization conditions.

Benefits of technology

It significantly improves the fast charging performance and high-rate discharge performance of the material, improves the energy density and cycle stability of the battery, and is suitable for battery applications with fast charging and discharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833593A_ABST
    Figure CN119833593A_ABST
Patent Text Reader

Abstract

The invention discloses a fast-charging type composite coated graphite negative electrode material and a preparation method thereof, and belongs to the field of lithium battery negative electrodes, and the method comprises the following steps: crushing dried raw material coke by using a crusher to obtain a first material, and shaping the first material by using a shaping machine to optimize the morphology of particles to obtain a second material; graphitizing the second material in a graphitization furnace to obtain a first graphite material; crushing the soft carbon precursor, dissolving the soft carbon precursor into a solvent, stirring and mixing to obtain a first coating agent, and uniformly mixing the first coating agent with the hard carbon precursor to obtain a second coating agent; mixing the first graphite material and a second coating agent, adding carbon nanotubes and / or graphene into the mixture, stirring to obtain a mixed material, carbonizing the mixed material under the protection of inert protective gas, and screening and demagnetizing the prepared material. According to the invention, the fast charging performance, the conductivity and the cycling stability of the graphite negative electrode material are improved through composite coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium battery negative electrodes, and in particular to a fast-charging composite coated graphite negative electrode material and a preparation method thereof. Background Art

[0002] Since its introduction in the early 1990s, lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density, high operating voltage, and good cycle stability. As electric vehicles continue to gain popularity and electronic products continue to be updated, people's requirements for lithium-ion batteries are getting higher and higher. Now, not only do we need batteries to be able to operate stably and safely, but we also have further requirements for their fast charging capabilities, requiring them to be fully charged in a shorter time to improve customer experience.

[0003] The fast charging capability of lithium-ion batteries is mainly limited by the negative electrode material. Currently, the most widely used negative electrode material in the lithium-ion battery industry is still graphite negative electrode. Although graphite negative electrode materials have become mature, in actual use, they have poor fast charging performance and are prone to lithium precipitation during low-temperature charging and discharging, which need to be urgently solved.

[0004] The prior art has reported that the method of coating graphite with a single soft carbon or a single hard carbon can improve the rate performance of the material, but soft carbon is easily graphitized, and its interlayer spacing will be further reduced during the carbonization or graphitization process, affecting its fast charging ability. In addition, the fast charging performance of soft carbon is lower than that of hard carbon, and the fast charging performance of a single soft carbon coating can no longer meet the growing demand for fast charging. When a single hard carbon is used for coating, since hard carbon is a difficult-to-graphitize material, after graphitization or carbonization, it will form a hard carbon with a larger interlayer spacing than that after asphalt carbonization, and the fast charging performance will be even better. However, the conductivity of the hard carbon material is poor and there are many surface defects. The formed negative electrode material has a large surface area, which can easily cause the first coulomb efficiency of the graphite negative electrode material to be low, affecting the cycle stability and capacity of the negative electrode material. Summary of the invention

[0005] One of the purposes of the present invention is to provide a fast-charging composite coated graphite negative electrode material and a preparation method thereof to solve the problem that the graphite negative electrode material in the prior art has insufficient fast-charging performance when coated with a single soft carbon, and has a large specific surface area when coated with a single hard carbon, resulting in low first coulombic efficiency, which affects the cycle stability and capacity of the negative electrode material.

[0006] The present invention is achieved through the following technical scheme, a method for preparing a fast-charging composite coated graphite negative electrode material, comprising the following steps: S100, drying raw coke, using a pulverizer to crush the dried raw coke to obtain a first material with a Dv50 of 5 to 13 μm, using a shaping machine to shape the first material to optimize the morphology of particles, and obtaining a second material with a Dv50 of 5.5 to 13.5 μm; S200, graphitizing the second material in a graphitization furnace to obtain a first graphite material with a particle size Dv50 of 5.5 to 9.5 μm; S300, crushing the soft carbon precursor to a particle size Dv50 of 1-6 μm, then dissolving the soft carbon precursor in a solvent and stirring and mixing for 10-240 min to obtain a first coating agent, wherein the mass ratio of the soft carbon precursor to the solvent is 1:0.1-0.6, and the first coating agent and the hard carbon precursor are uniformly mixed in a mass ratio of 1:0.3-0.8 to obtain a second coating agent; S400, mixing the first graphite material and the second coating agent, and adding carbon nanotubes and / or graphene to the mixture and stirring and mixing for 5-50 min. min to obtain a mixed material, and carbonize the mixed material under the protection of an inert protective gas, the carbonization temperature is 800-1700°C, and the mass ratio of the first graphite material, the second coating agent, and the carbon nanotube and / or graphene is 1:0.02-0.15:0.001-0.01; S500, after the carbonization treatment is completed, the prepared material is screened and demagnetized using a sieve with an aperture of 200-400 mesh.

[0007] Furthermore, the drying temperature of the dried raw coke is 80-120°C, and the moisture content of the raw coke after drying is ≤6% by mass; the raw coke includes one or more combinations of petroleum coke, needle coke and asphalt coke; the mass percentage of volatile components in the raw coke is 3%-15%, wherein the mass percentage of volatile components in needle coke is 3%-8%, the mass percentage of volatile components in petroleum coke is 7%-15%, and the mass percentage of volatile components in asphalt coke is 5%-9%.

[0008] Furthermore, the graphitization furnace is a crucible furnace or a box furnace, the temperature of the graphitization furnace is 2700-3200°C; the time for the temperature to rise to 2700-3200°C is 10-40h; and the graphitization time is 20-40 days.

[0009] Furthermore, the soft carbon precursor is a combination of one or more of coal-based asphalt, petroleum-based asphalt or natural asphalt having a softening point of 100-350°C.

[0010] Furthermore, the hard carbon precursor is one or more combinations of phenolic resin, epoxy resin, furfural resin, acrylic resin, furan resin, polyvinyl alcohol, chitosan, styrene-butadiene rubber, and glucose.

[0011] Furthermore, the solvent is a combination of one or more organic solvents such as benzene, toluene, xylene, chlorobenzene, dichlorobenzene, washing oil, tetrahydrofuran, etc.

[0012] Furthermore, the heating rate of the carbonization treatment is 0.5-10°C / min, and the calcination time is 190min-3120min.

[0013] Furthermore, the inert protective gas includes a combination of one or more of nitrogen, helium, neon, argon, krypton, and xenon, and the flow rate of the inert protective gas is 2-10 mL / min.

[0014] Another aspect of the present invention provides a fast-charging composite coated graphite negative electrode material, which is obtained according to the preparation method described above. The graphite negative electrode material has a particle size Dv50 of 8-18.0 μm, a magnetic foreign matter content of <1 ppm, and a specific surface area of ​​<2.5 m2 / g.

[0015] The present invention also provides a lithium battery, the negative electrode of which contains the fast-charging composite coated graphite negative electrode material as described above.

[0016] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0017] 1. The composite coated artificial graphite negative electrode material provided by the present invention is coated with a layer of soft and hard carbon composite material on the surface of a single graphite particle, and a certain amount of carbon nanotubes and / or graphene is added to improve the fast charging performance of the material. It has excellent rate performance and high capacity retention rate in a low temperature environment, and the production process is simple, the product properties are stable, and large-scale mass production can be achieved.

[0018] 2. The graphite negative electrode material of the present invention has excellent electrochemical properties and a high first charge and discharge efficiency. Under the same volume or mass, the lithium-ion battery prepared by the graphite negative electrode material prepared by the present invention can store more electrical energy and improve the overall energy density of the battery. At the same time, it has a higher reversible capacity during the first charge and discharge process, reduces the capacity loss caused by irreversible reactions, and improves the battery life. And the high-rate capacity retention rate of the lithium-ion battery prepared by the graphite negative electrode material of the present invention reflects the stability of the material of the present invention at high current density, and is suitable for application in batteries that require fast charging and discharging, such as power batteries and high-power equipment.

[0019] 3. The preparation method of the fast-charging composite coated graphite negative electrode material provided by the present invention ensures the excellent electrochemical performance of the final product by optimizing the particle size, accurately controlling the graphitization and carbonization conditions, adopting the composite coating technology and strict post-processing steps, and is particularly suitable for the production of high-performance battery negative electrode materials. These advantages make this method have significant advantages in improving the fast-charging performance of materials, reducing production costs and enhancing product consistency.

[0020] 4. The present invention adopts a composite coating of soft carbon and hard carbon, combined with carbon nanotubes and / or graphene, which significantly improves the conductivity and stability of the material finally prepared, and achieves improvements in fast charging performance and high-rate discharge performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:

[0022] Figure 1 This is a particle size distribution diagram of the fast-charging composite coated graphite negative electrode material prepared in Example 1 of the present invention.

[0023] Figure 2 This is a scanning electron microscope image of the fast-charging composite coated graphite negative electrode material prepared in Example 1 of the present invention.

[0024] Figure 3 This is the XRD diagram of the fast-charging composite coated graphite negative electrode material prepared in Example 1 of the present invention.

[0025] Figure 4 This is a transmission electron microscope image of the fast-charging composite coated graphite negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations. In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.

[0027] Embodiment 1,

[0028] This embodiment discloses a method for preparing a fast-charging composite coated graphite negative electrode material, and the specific implementation scheme includes the following steps:

[0029] Step 1: Use needle coke with volatile matter of 3% to 8% as raw material, dry the blocky needle coke raw material at 80°C for 12 hours, and obtain a dried raw material with a moisture content of 0.5% to 1.5%. The dried needle coke is crushed using a pulverizer, and the Dv50 of the crushed material is 6μm. Then, a shaping machine is used to shape the crushed material, and the particle size of the shaped material is Dv50=6.5μm to obtain the shaped material. Finally, the shaped material is graphitized in a crucible furnace to obtain a single-particle artificial graphite material. The Dv50 of the single-particle artificial graphite material is 8.5μm. The temperature of the graphitization process is 3000°C, and the time for the graphitization treatment temperature to rise to 2700°C is 15h; the entire graphitization treatment time is 35 days.

[0030] Step 2: Use a crusher to crush the petroleum asphalt with a softening point of 200°C to obtain an asphalt powder with Dv50=2 μm. Use toluene to dissolve the obtained asphalt powder to obtain a liquid soft carbon coating agent. The mass ratio of asphalt to toluene is 3:7, the dissolution temperature is 70°C, and the stirring time during dissolution is 60 minutes. Then the soft carbon coating agent is mixed with phenolic resin in a ratio of 5:5 and stirred for 60 minutes to obtain a soft / hard carbon composite coating agent.

[0031] Step 3: The single-particle artificial graphite material in step 1, the soft / hard carbon coating agent in step 2 and the carbon nanotubes are mixed in a fusion machine at a ratio of 1:0.069:0.005, the fusion machine speed is 400r / min, and the mixing time is 30 min. The above-mentioned mixed material is carbonized in a carbonization furnace under nitrogen gas protection. The carbonization temperature is 1450℃, the carbonization heating rate is 3℃ / min, and the time is 600 min.

[0032] The carbonized material in step 3 is sieved with 325 mesh and then demagnetized to obtain the fast-charging composite coated artificial graphite negative electrode material of Example 1. The particle size of the prepared fast-charging composite coated graphite negative electrode material is Dv10=3.9μm, Dv50=12.5μm, and Dv100=33.5μm.

[0033] Figure 1 This is the particle size distribution diagram of the fast-charging composite coated graphite negative electrode material of this embodiment. It can be seen from the figure that the cumulative curve of the particle size distribution (blue): the blue curve shows the corresponding cumulative percentage of each particle size. The curve gradually reaches 100% from the lower left to the upper right, indicating that the particle size gradually accumulates from the smallest to the largest. At a particle size of 12.54μm (ie, D50), the cumulative percentage is about 50%, indicating that half of the particles have a diameter of ≤12.54μm. At a particle size of 22.48μm (ie, D90), the cumulative percentage reaches 90%, indicating that 90% of the particles have a diameter of ≤22.48μm.

[0034] Difference curve of particle size distribution (red): The red curve shows the percentage distribution of particles in different particle size ranges (Diff%), and the peak value indicates the concentration of particles in a certain particle size range. The main distribution range of particle size is between 10μm and 20μm, and the peak value appears in the range of 10μm to 20μm (52.00%), indicating that the particle distribution in this range is the most dense. The second highest distribution is concentrated in the range of 5μm to 10μm, with a content of 27.64%.

[0035] The tabular data in the figure show that the vast majority of particles are distributed between 5μm and 45μm, of which particles in the range of 5μm to 10μm account for 27.64%, particles in the range of 10μm to 20μm account for 52.00%, and particles in the range of 20μm to 45μm account for 15.57%.

[0036] The content of particles with a particle size less than 1 μm is almost zero (0.00%), and particles with a particle size greater than 45 are also not seen, indicating that the particle size distribution of the graphite negative electrode material prepared by the steps of this embodiment is relatively concentrated and has good uniformity.

[0037] Figure 2 This is a scanning electron microscope image of the fast-charging composite coated graphite negative electrode material of this embodiment. It can be seen from the figure that the graphite negative electrode material particles prepared in this embodiment are evenly distributed, which conforms to the narrow particle size distribution obtained in the particle size distribution analysis. At the same time, the size and shape of each particle are similar, and the surface is relatively smooth, indicating that the material has been carefully prepared and shaped.

[0038] Although the SEM image cannot directly distinguish the soft carbon and hard carbon coating layers, the smooth surface of the graphite particles and the lack of obvious coating protrusions indicate that the coating is uniform and good. This uniform composite coating improves the conductive network and mechanical stability, which helps to improve the overall performance of the battery.

[0039] It can be clearly seen from the figure that the particle size is moderate and uniform, which matches the particle size distribution data. The particles are uniform in size and packed tightly together, which also clearly shows that they are well controlled in the steps of crushing, shaping and grading and screening.

[0040] Figure 3 This is the XRD diagram of the fast-charging composite coated graphite negative electrode material of this embodiment. The horizontal axis (2θ / °) in the figure represents the X-ray diffraction angle in degrees (°). The vertical axis (Intensity / au) represents the intensity of the diffraction peak in arbitrary units (au, arbitrary units).

[0041] Main diffraction peak 2θ ≈ 26.5°: This is a characteristic peak of graphite material, usually corresponding to the diffraction peak of the (002) plane, representing the layered structure of graphite. 2θ ≈ 43.5°: Corresponding to the characteristic peak of the graphite (100) plane, showing the stacking of graphite layers.

[0042] As can be seen from the figure, the high-intensity (002) peak is a characteristic peak of graphite materials, indicating the presence of graphite layer structure. The appearance of this peak indicates that the composite graphite material has a highly ordered layered structure. The strong and sharp (002) peak shows a high degree of crystal structure perfection, which means that the material has a good degree of graphitization, which helps to improve the conductivity and stability of the battery.

[0043] (100) diffraction peak (2θ ≈ 43.5°) This peak represents the interlayer stacking and crystal plane arrangement in other directions of graphite. The appearance and intensity of this diffraction peak show that the material not only has a layered arrangement in a two-dimensional plane, but also has a highly ordered stacking structure in a three-dimensional direction.

[0044] Although a small amount of impurity peaks can be seen in the figure, the peak around 28.425° and other impurity peaks in the figure are peaks of silicon powder. Silicon powder is usually added to revise the peak position during XRD testing of graphite materials, and the offset value of 28.425° of silicon powder is used to correct the peak of graphitized material. In other words, the main diffraction peaks (26.5° and 43.5°) in the figure show that the material is still mainly graphite, and the composite coating structure does not significantly interfere with the crystal structure of graphite.

[0045] Figure 4 This is a transmission electron microscope image of the fast-charging composite coated graphite negative electrode material of this embodiment. It can be seen from the figure that the left side of the image shows an area with a larger interlayer spacing, which should be the soft carbon or hard carbon layer coated on the outside of the graphite. In the coating layer, the interlayer spacing is large and the structure is loose, which is a typical soft carbon or hard carbon feature. The presence of the coating layer can provide some additional advantages, such as enhancing the structural stability and conductivity of the material.

[0046] The right part of the image shows the area with smaller interlayer spacing and dense arrangement, which is the graphite layer with a higher degree of graphitization. The graphitized layer has a highly ordered layered structure with a small interlayer spacing, usually around 0.33 nanometers, which is a typical feature of graphite materials. This dense graphite layer provides excellent electrochemical properties, including high conductivity and high capacity.

[0047] The middle area of ​​the image shows the transition area between the graphite layer and the coating layer. The relatively clear interface transition indicates that the coating layer is well combined with the graphite body, without obvious interface defects, showing high interface quality and excellent structural stability. Such an interface structure can effectively reduce the volume change of the material during the charge and discharge process, and improve the cycle life and structural stability.

[0048] Embodiment 2,

[0049] This embodiment discloses a method for preparing a fast-charging composite coated graphite negative electrode material, the main steps of which are consistent with those of embodiment 1, except that:

[0050] The raw material coke used in this embodiment is petroleum coke with a volatile component of 7% to 15%, which is dried at 120° C. for 9 hours to obtain a dried raw material with a moisture content of 1% to 2.5%.

[0051] The soft carbon precursor used in this embodiment is coal-based pitch with a softening point of 150° C. The solvent is xylene, and the mass ratio of coal-based pitch to xylene is 2:8. The hard carbon precursor is furfural resin.

[0052] The particle sizes of the fast-charging composite coated graphite negative electrode material finally prepared in this embodiment are Dv10=3.9 μm, Dv50=12.5 μm, and Dv100=33.5 μm.

[0053] Embodiment 3,

[0054] This embodiment discloses a method for preparing a fast-charging composite coated graphite negative electrode material, the main steps of which are consistent with those of embodiment 1, except that:

[0055] The raw material coke used in this embodiment is pitch coke with a volatile component of 5% to 9%, which is dried at 100° C. for 10 hours to obtain a dried raw material with a moisture content of 0.5% to 1.5% by mass.

[0056] The soft carbon precursor used in this embodiment is natural asphalt with a softening point of 300° C. The solvent is dichlorobenzene and the hard carbon precursor is chitosan.

[0057] The particle sizes of the fast-charging composite coated graphite negative electrode material finally prepared in this embodiment are Dv10=3.7 μm, Dv50=12.3 μm, and Dv100=32.8 μm.

[0058] Embodiment 4,

[0059] The present embodiment discloses a method for preparing a fast-charging composite coated graphite negative electrode material, the main steps of which are consistent with those of Example 1, except that in step 2, the asphalt is replaced with a petroleum-based asphalt having a softening point of 180°C, and the other conditions and parameters are the same as those of Example 1. The particle size of the prepared fast-charging composite coated graphite negative electrode material is Dv10=3.2μm, Dv50=11.3μm, and Dv100=29.5μm.

[0060] Comparative Example 1

[0061] Step 1: Use needle coke with volatile matter of 3% to 8% as raw material, dry the blocky needle coke raw material at 80°C for 12 hours, and obtain a dried raw material with a moisture content of 0.5% to 1.5%. The dried needle coke is crushed using a pulverizer, and the Dv50 of the crushed material is 6~8μm. Then, a shaping machine is used to shape the crushed material, and the particle size of the shaped material is Dv50=6.5~8.5μm to obtain the shaped material. Finally, the shaped material is graphitized in a crucible furnace to obtain a single-particle artificial graphite material. The final particle size of the single-particle artificial graphite material is Dv10=2.5μm; Dv50=8.5μm; D90=23.5μm. The temperature of the graphitization process is 3000-3200°C, and the time for the graphitization temperature to rise to 2700-3200°C is 15-40 hours; the entire graphitization treatment time is 25-35 days.

[0062] Step 2: Use a crusher to crush petroleum-based asphalt with a softening point of 200°C to obtain asphalt powder with a Dv50 of 2 μm. Use toluene to dissolve the obtained asphalt powder to obtain a liquid soft carbon coating agent.

[0063] Step 3: The single-particle artificial graphite material in step 1, the soft carbon coating agent in step 2 and the carbon nanotubes are mixed in a fusion machine at a ratio of 1:0.069:0.005, the fusion machine speed is 400r / min, and the mixing time is 30 min. The above-mentioned mixed material is carbonized in a carbonization furnace under nitrogen gas protection. The carbonization temperature is 1450℃, the carbonization heating rate is 3℃ / min, and the time is 600 min.

[0064] The material finally prepared is the graphite negative electrode material of this comparative example.

[0065] Comparative Example 2

[0066] Step 1: Use needle coke with volatile matter of 3% to 8% as raw material, dry the blocky needle coke raw material at 80°C for 12 hours, and obtain a dried raw material with a moisture content of 0.5% to 1.5%. The dried needle coke is crushed using a pulverizer, and the Dv50 of the crushed material is 6 to 8 μm. Then, a shaping machine is used to shape the crushed material, and the particle size of the shaped material is Dv50 = 6.5 to 8.5 μm to obtain the shaped material. Finally, the shaped material is graphitized in a crucible furnace to obtain a single-particle artificial graphite material. The final particle size of the single-particle artificial graphite material is Dv10 = 2.5 μm; Dv50 = 8.5 μm; Dv90 = 23.5 μm. The temperature of the graphitization process is 3000-3200°C, and the time for the graphitization temperature to rise to 2700-3200°C is 15-40 hours; the entire graphitization treatment time is 25-35 days.

[0067] Step 2: The single-particle artificial graphite material, phenolic resin and carbon nanotubes in step 1 are mixed in a fusion machine at a ratio of 1:0.069:0.005, the fusion machine speed is 400r / min, and the mixing time is 30 min. The above-mentioned mixed material is carbonized in a carbonization furnace under nitrogen gas protection. The carbonization temperature is 1450℃, the carbonization heating rate is 3℃ / min, and the time is 600 min.

[0068] The carbonized material in step 3 is sieved with 325 mesh and then demagnetized to obtain the fast-charging composite coated artificial graphite negative electrode material of Example 1. The particle size of the prepared artificial graphite negative electrode material is Dv10=3.9 μm, Dv50=12.9 μm, and Dv100=33.8 μm.

[0069] Comparative Example 3

[0070] Step 1 uses needle coke with a volatile content of 3% to 8% as a raw material, and dries the lump of needle coke raw material at 80°C for 12 hours to obtain a dried raw material with a moisture content of 0.5% to 1.5%. The dried needle coke is crushed using a pulverizer, and the Dv50 of the crushed material is 6 to 8 μm. Then, a shaping machine is used to shape the crushed material, and the particle size of the shaped material is Dv50 = 6.5 to 8.5 μm to obtain the shaped material. Finally, the shaped material is graphitized in a crucible furnace to obtain a single-particle artificial graphite material. The final particle size of the single-particle artificial graphite material is Dv10 = 2.5 μm; Dv50 = 8.5 μm; Dv90 = 23.5 μm. The temperature of the graphitization process is 3000-3200°C, and the time for the graphitization temperature to rise to 2700-3200°C is 15-40 hours; the entire graphitization treatment time is 25-35 days.

[0071] Step 2: The graphitized material is sieved using 325 mesh, and then subjected to demagnetization treatment to obtain the graphite negative electrode material of this comparative example.

[0072] Experimental example

[0073] The graphite negative electrode materials in the above-mentioned embodiments and comparative examples were made into lithium-ion batteries and subjected to performance tests. The experimental results and test data of the graphite negative electrode materials are shown in Table 1.

[0074] Table 1. Experimental results and test data of graphite negative electrode materials

[0075] name Particle size / Dv50μm <![CDATA[Vibrating compaction / gcm -2 > <![CDATA[Specific surface area / gcm -3 > Graphitization degree / % <![CDATA[Specific capacity / mAh g -1 > First effect / % 1C rate discharge capacity retention rate / % 2C rate discharge capacity retention rate / % Example 1 12.54 1.02 1.79 93.75% 356.56 91.93 89 59 Example 2 12.86 0.98 1.99 93.67% 356.89 91.15 81 50 Example 3 12.39 1.00 1.61 93.27% 354.86 91.70 78 47 Example 4 11.36 1.01 1.82 93.76% 356.43 91.65 83 51 Comparative Example 1 11.92 1.04 1.36 93.65% 355.56 92.65 75 43 Comparative Example 2 12.94 0.96 1.96 93.57% 356.36 91.03 82 47 Comparative Example 3 8.5 1.25 2.35 94.79% 360.25 94.08 50 32

[0076] As can be seen from the above table, in Example 1, Comparative Example 1 and Comparative Example 2, the fast charging performance of the material coated with soft / hard carbon is better than that of the pure soft carbon coated material and the pure hard carbon coated material. And comparing Example 1, Example 2 and Example 3, the effect of mixing the soft carbon coating agent and the phenolic resin in a ratio of 5:5 is the best. Comparing Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3, the fast charging performance of the single-particle graphite material not coated with soft carbon or hard carbon is significantly lower than that of the material coated with soft carbon or hard carbon. After graphitization or carbonization, the material coated with soft carbon or hard carbon will form a lattice with a larger interlayer spacing compared to the surface of the uncoated material, resulting in a faster transmission speed of lithium ions in the material, resulting in a significant improvement in its fast charging performance. After carbonization, hard carbon materials such as resins will form hard carbon with a larger interlayer spacing than asphalt after carbonization, and the fast charging performance is greater than that of asphalt-coated materials. Therefore, the fast charging performance of soft / hard carbon-coated materials is higher than that of soft carbon-coated materials. The hard carbon material has many surface defects, resulting in a larger negative electrode material specific surface area, which leads to a low initial efficiency of the material. In addition, the poor electronic conductivity of the hard carbon material affects the material's electronic transmission ability and the material's fast charging performance, resulting in the fast charging performance of the pure hard carbon coated material being lower than that of the soft / hard carbon coated material. Therefore, the comprehensive performance of the soft / hard carbon coated material is better than that of the pure soft carbon or hard carbon coated material.

[0077] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a fast-charging composite coated graphite negative electrode material, characterized in that: The preparation method comprises: S100, drying the raw coke, crushing the dried raw coke with a pulverizer to obtain a first material with a Dv50 of 5 to 13 μm, and using a shaping machine to shape the first material and optimize the morphology of the particles to obtain a second material with a Dv50 of 5.5 to 13.5 μm; S200, placing the second material in a graphitization furnace for graphitization to obtain a first graphite material with a particle size Dv50 of 5.5-9.5 μm; S300, crushing the soft carbon precursor to a particle size Dv50 of 1-6 μm, then dissolving the soft carbon precursor in a solvent and stirring and mixing for 10-240 min to obtain a first coating agent, wherein the mass ratio of the soft carbon precursor to the solvent is 1:0.1-0.6, The first coating agent and the hard carbon precursor are uniformly mixed in a mass ratio of 1:0.3 to 0.8 to obtain a second coating agent; S400, mixing the first graphite material and the second coating agent, adding carbon nanotubes and / or graphene to the mixture, stirring and mixing for 5 to 50 minutes to obtain a mixed material, and carbonizing the mixed material under an inert protective gas environment at a carbonization temperature of 800 to 1700° C., The mass ratio of the first graphite material, the second coating agent and the carbon nanotube and / or graphene is 1:0.02-0.15:0.001-0.01; S500: After the carbonization treatment is completed, the prepared material is screened and demagnetized using a sieve with an aperture of 200-400 mesh.

2. The method for preparing the fast-charging composite coated graphite negative electrode material according to claim 1, characterized in that: The drying temperature of the dried raw coke is 80-120°C, and the moisture content of the raw coke after drying is ≤6% by mass; The raw coke includes one or more of petroleum coke, needle coke and pitch coke; The mass percentage of volatile components in the raw coke is 3% to 15%, wherein: The mass percentage of volatile components in needle coke is 3% to 8%. The mass percentage of volatile components in petroleum coke is 7% to 15%. The mass percentage of volatile components in pitch coke is 5% to 9%.

3. The method for preparing the fast-charging composite coated graphite negative electrode material according to claim 1, characterized in that: The graphitization furnace is a crucible furnace or a box furnace, the temperature of the graphitization furnace is 2700-3200° C.; the time for the temperature to rise to 2700-3200° C. is 10-40 hours; and the graphitization time is 20-40 days.

4. The method for preparing the fast-charging composite coated graphite negative electrode material according to claim 1, characterized in that: The softening point of the soft carbon precursor is 100-350° C., and the soft carbon precursor is a combination of one or more of coal-based asphalt, petroleum-based asphalt or natural asphalt.

5. The method for preparing the fast-charging composite coated graphite negative electrode material according to claim 1, characterized in that: The hard carbon precursor is one or more combinations of phenolic resin, epoxy resin, furfural resin, acrylic resin, furan resin, polyvinyl alcohol, chitosan, styrene-butadiene rubber and glucose.

6. The method for preparing the fast-charging composite coated graphite negative electrode material according to claim 1, characterized in that: The solvent is a combination of one or more organic solvents such as benzene, toluene, xylene, chlorobenzene, dichlorobenzene, washing oil, tetrahydrofuran, etc.

7. The method for preparing the fast-charging composite coated graphite negative electrode material according to claim 1, characterized in that: The heating rate of the carbonization treatment is 0.5-10°C / min, and the calcination time is 190-3120min.

8. The method for preparing the fast-charging composite coated graphite negative electrode material according to claim 1, characterized in that: The inert protective gas includes one or more of nitrogen, helium, neon, argon, krypton and xenon. The flow rate of the inert protective gas is 2~10 mL / min.

9. A fast-charging composite coated graphite negative electrode material, characterized in that: The graphite negative electrode material is obtained according to the preparation method according to any one of claims 1 to 8, wherein the graphite negative electrode material has a particle size Dv50 = 8 to 18.0 μm, a magnetic foreign matter content of <1 ppm, and a specific surface area of ​​<2.5 m2 / g.

10. A lithium battery, characterized in that: The negative electrode contains the fast-charging composite coated graphite negative electrode material as claimed in claim 9.

Citation Information

Cited By

  • Composite binder, preparation process of artificial graphite, artificial graphite and application

    CN120664889A